THE APPLICATION OF DIFFERENTIATED LEARNING IN IMPROVING STUDENTS' LEARNING ACTIVENESS AND CREATIVITY - Rosalina Hutbah Ritonga; Halimatusyakdiyah (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
In the 21st Century, the independent learning curriculum is in the spotlight for the world of education, the learning process of students is required to be more active and teachers are required to be able to meet the needs of students and increase the potential of students such as talents, interests and creativity. One solution to meet the needs of students is the application of differentiated learning. Differentiated learning aims to provide facilities for the diversity of students based on the learning needs and characteristics of students. This study aims to determine whether the application of content and product differentiation learning can increase student learning activity and creativity. This type of research is Classroom Action Research (CAR) using a qualitative approach. The research results obtained are increased activity and creativity of students from the implementation of differentiated learning content and products using cooperative learning models, while judging from the results of observations, students as a whole are very actively involved during the learning process, making products to show the results of their discussions in front of the class.